(untitled) (Global Journal of Science Frontier Research, 2015)
The comparison of the contribution of agricultural sector and industrial sector towards the development/growths in the Nigerian economy between 2005-2014 were determined using Hoteling T-distribution procedure. The data were collected from National Population Bureau of Statistics (NBS) and two populations were studied, namely agricultural sector and industrial sector. Under these two populations, four samples were selected from each population. For agricultural sector, the samples selected were crop production, livestock, forestry and fishing. For industrial sector, the samples selected were quarrying and other minerals, oil refining, cement and other manufacturing. The analysis shows that both sectors contribute to the development/growth of the Nigerian economy and the hypothesis were tested to know their level of contribution towards the growth/development of the Nigerian economy, which also shows that agricultural sector, contributes more to the economy than the industrial sector.